Extraction Method of Extreme Rainfall Data - Roslinazairimah, Zakaria; Noor Fadhilah, Ahmad Radi; Siti Zanariah, Satari (IOP Publishing, 2017)
This study is aimed to describe step by step procedure in extracting extreme rainfall data series. Basically, the extraction of extreme rainfall data can be achieved using two methods, block maxima (BM) and peak over threshold (POT) methods. The BM method considers extracting the extreme rainfall data recorded each year during a specific duration, meanwhile the POT method is extracting all extreme rainfall data above a predefined threshold. Using the BM method, the regional pooling of 1-, 3-, 5- and 10-day are used and the maximum rainfall data are chosen among the pooled day within each year. For POT method, two methods are presented. Method 1 of POT method determines a threshold based on 95% percentile while Method 2 determines the threshold graphically using mean residual life plot and threshold stability plot. Based on the selection of the threshold value, a simulation study is conducted to identify the range of appropriate quantile estimate for a proper selection of the threshold value. For illustration of the methodology, daily rainfall data from the rainfall station at Klinik Chalok Barat, Terengganu is chosen. Both methods used are able to identify the extreme rainfall series. This study is important as it helps in identifying the good set of extreme rainfall series for further use such as in extreme rainfall modelling.